Renaud Paulian et le programme du CNRS sur les hautes montagnes à Madagascar: étage vs domaine - Guillaumet, Jean-Louis (2008)
The project entitled “Study of montane ecosystems in the Malagasy region” (RCP 225/CNRS, directed by Renaud Paulian) aimed to elucidate the general features of these ecosystems and the origin of their constituent elements, and to test the validity of the High Mountain Domain proposed by Humbert in 1951. From 1970 to 1973, three expeditions (to the Andringitra, Anosy, Ankaratra, Itremo, Ibity and Marojejy massifs) provided informations to characterize the ecology of these particular environments and to analyse systematically certain groups well-known for their biogeographic interest. The altitudinal succession of plant formations, defined by physiognomic and structural criteria, were detailed for each massif. The highest belt, characterized by an ericoid bush and related associations, does not correspond to the High Mountain formation of East Africa. Data on several faunal groups, including invertebrates (Hexapoda: Collembola and Dermaptera), indicate a disjunction between the northern montane massifs (Tsaratanana and Marojejy) and the remainder in the Center and South; several floristic groups (Pandanaceae, Araliaceae and Asteraceae) are currently being analyzed in a similar manner. Madagascar's High Mountain Domain is an ecological reality, but it can not be defined floristically, as each massif represents a separate phytogeographic entity with interdependent vegetation belts included within the various sub-domains of the island's Central Domain. Faunal groups with limited mobility broadly indicate a trophic and bioclimatic dependence (buffer effect of the intra-forest climate) with regard to vegetation belt, but can respond to local microclimates by a shift at the limits of their ranges.